2019
DOI: 10.1002/aocs.12302
|View full text |Cite
|
Sign up to set email alerts
|

Glycidols Esters, 2‐Chloropropane‐1,3‐Diols, and 3‐Chloropropane‐1,2‐Diols Contents in Real Olive Oil Samples and their Relation with Diacylglycerols

Abstract: A series of authentic virgin, refined, and mixtures of olive oils was analyzed for their content of 2‐and 3‐chloropropanediol (MCPD) esters expressed as 2−/3‐MCPD, glycidol (and related glycidyl esters) (GE), and diglycerides (DAG). High concentrations of MCPD and GE were found, above all, in pomace oils, which come from the poorer starting raw materials, while virgin olive oils, as expected, do not contain any process contaminant. On the other hand, DAGs are present in all samples, demonstrating that their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The order of the effects was duration > temperature > DAG content. The previous studies also found that the role of DAG in the formation of 3-MCPDE and GE was not clear, but high temperature was indeed the key factor [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The order of the effects was duration > temperature > DAG content. The previous studies also found that the role of DAG in the formation of 3-MCPDE and GE was not clear, but high temperature was indeed the key factor [ 33 ].…”
Section: Discussionmentioning
confidence: 99%